The melamine milk crisis in China - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case concerns the business ethics of companies who knowingly put their customers in danger in order to make greater profits. Using the example of the Sanlu Group in China, which added dangerous melamine to its milk products, this case also asks what the responsibility of international firms is to police their partners.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). The Melamine Milk Crisis in China. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 282-284). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Business ethics -- Case studies; Food contamination -- China -- Case studies